The Role of Government Internal Control Systems and Utilization of Information Technology in Quality Reports - Evelytha Goutama; Ivan Yudianto (Universitas Padjadjaran, 2019)
This study aims to determine how the implementation of the government internal control system and the use of information technology in improving the quality of local-owned asset reports in the Government of West Bandung Regency, Bandung City, and Subang Regency. This study uses qualitative methods, and data collection is done by interview and documentation techniques to 12 informants who are Heads of Asset Fields in Financial and Asset Management Agency of Bandung City, Subang Regency, and West Bandung Regency. Data analysis is done by reducing data and then presenting data and drawing conclusions on data obtained according to the method of data analysis for qualitative research. The results showed that the implementation of the government internal control system and the use of information technology in improving the quality of reports on local-owned asset reports in Government of Bandung City, Subang Regency, and West Bandung Regency were well implemented. Each region has problems related to the management of the different local-owned asset.